New bothremydid turtle (Testudines, Pleurodira) from the paleocene of northeastern Colombia (2012)
A new turtle, Puentemys mushaisaensis, from the middle to late Paleocene Cerrejón Formation of Colombia, is described on the basis of a partial skull and many partial to nearly complete carapaces and plastrons representing multiple ontogenetic stages. Whereas P. mushaisaensis is unique in aspects of its shell morphology, it shares many diagnostic characteristics of bothremydid pleurodirans, including a long exoccipital-quadrate contact, a very low and rounded almost circular carapace, and a thinner internal bone cortex than that of the external cortex in both the carapace and plastron. With a maximum carapacial length of 151 cm, P. mushaisaensis is the largest known bothremydid turtle and represents the first occurrence of bothremydids in the Paleogene of South American tropics. Results from a cladistic analysis of bothremydids indicate that P. mushaisaensis shares a close relationship with Foxemys mechinorum from the Late Cretaceous of Europe, indicating a wide-spread geographical distribution for bothremydines during the Late Cretaceous–Paleocene.